Longinischus ornatus, a new genus and new species of Ozophorini (Hemiptera: Heteroptera: Lygaeoidea: Rhyparochromidae: Rhyparochrominae) from Guatemala - Brailovsky, Harry (Zootaxa, 2009)
Until recently, Guatemalan Ozophorini (Heteroptera: Lygaeidae: Rhyparochromidae) have been largely neglected and their diversity in the region is poorly known. Ashlock & Slater (1982), Slater (1964, 1999) and Slater & O’Donnell (1995) list three genera and nine species for that region: Balboa germana (Distant), Balboa variabilis Distant, Lygofuscanellus alboannulatus (Champion), Lygofuscanellus ozophoroides Slater, Ozophora concava Distant, Ozophora maculata Slater & O’Donnell, Ozophora parapicta Slater & Hassey, Ozophora rubrolinea Slater, and Ozophora vasquezae Slater.